Transmission Timing and Synchronization Control for Energy-Efficient Multi-Hop LoRaWAN - Hiroto Shida; Aoto Kaburaki; Koichi Adachi (IEEE Access)
LoRaWAN (Long Range Wide Area Network), a type of LPWAN (Low Power Wide Area Network), has gained popularity for enabling long-distance data transmission with low-power consumption. However, single-hop LoRaWAN may not be able to provide a sufficiently wide communication range in a practical environment. Although multi-hop communication can offer a wider communication range in LoRaWAN, it has its distinct challenges: the hidden node problem, synchronization misalignment, throughput degradation, and increased power consumption due to noncentralized operation. This paper aims to solve those challenges by proposing an autonomous distributed adaptive resource allocation method and a synchronization misalignment compensation method for multi-hop LoRaWAN systems. In the proposed method, each device selects the radio resource, i.e., time slot and frequency channel, for packet transmission through a mapping rule shared among the devices in advance. Since each device can calculate the timing of the current packet transmission from its preceding device, it can compensate for the misalignment of synchronization. Furthermore, predicting the timing of the next packet from the preceding device enables the device to open the receive window during that time only. Thus, this resource selection not only helps avoid packet collisions but also reduces power consumption by preventing unnecessary reception window openings, thereby improving the efficiency of LoRaWAN communication. The proposed methods are implemented in commercially available private LoRa systems to show their potential to reduce device power consumption by up to 50% reduction.